Challenges for corporate governance in the digital age: new risks of data loss and privacy - Davletbayeva, N.B.; Nurseit, T.A.; Takuova, Z.S. (Академик Е.А.Бөкетов атындағы Қарағанды университетінің баспасы, 2024)
The article "Challenges for corporate governance in the digital age: new risks of data loss and privacy" discusses the major issues related to data loss management and privacy violation management, considering the digital transformation of the Kazakhstani economy. The group emphasizes that detailed risk management approaches should be developed by analyzing modern risks such as cyberattacks, data leaks, and a lack of awareness among staff members. Particular consideration is given to the application of contemporary technology, such as blockchain and artificial intelligence, employee training, and the application of international standards like ISO 27001. In conclusion, the authors emphasize the strengthening of the regulatory framework, the necessity of intersectoral cooperation for improving the sustainability of the digital economy. The recommendations deal with the implementation of the information security management systems, the creation of national plans in order to reduce the risks and create a competitive economy.
Keywords: digital transformation; data loss; data confidentiality; risk management; cybersecurity; artificial intelligence; digital economy; information security; corporate governance; cyberattacks; regulatory compliance